Perancangan Oven Steamer dan Sistem Boiler untuk Meningkatkan Efisiensi Sterilisasi Baglog Jamur Tiram Putih - Iwan Iswanto, Agus; Anisa, Nurfa; Budi Santoso, Asih (JATI UNIK : Jurnal Ilmiah Teknik dan Manajemen Industri, 2025)
White oyster mushroom cultivation in Indonesia faces obstacles to the efficiency of the planting media sterilization process (baglog), especially for medium-scale farmers. This research aims to design a steamer oven with a capacity of 1,200 baglogs that is efficient and according to operational needs in the field. The method used is a theoretical simulation-based engineering design, including the analysis of energy needs, steam capacity, oven dimensions, and sterilization time. The oven design uses a water tube type boiler system that is integrated with the combustion chamber and equipped with a one-way steam circulation system. The simulation results showed that the sterilization process could be completed in ±4.73 hours with better fuel efficiency compared to conventional methods. These findings show significant potential in increasing the productivity and efficiency of the oyster mushroom cultivation process. However, further implementation through prototyping and field trials is required to validate the actual performance of the tool. This design is expected to be a reference for simple technology-based farming tool innovation in the agricultural sector.